You’re Earthbound - Gaëtan Le Coarer (The Journal of Studies in Language, Culture and Society, 2024)
AN DOMHAN, is an adaptation of an Irish Celtic legend in the mixed (XR) of a virtual reality (VR) and augmented reality (AR) device. How can we bridge the gap between a spatially adapted narrative process in an immersive device and a sensitive, fictitious, legendary heritage resource? The article explores a methodological and phenomenological trajectory between usage analysis (XR) and the implementation of an Earth that augurs the incorporeal scope of heritage.